Meliola samaderae sp. nov. from Kerala - C.K. BIJU and P. PONNUSWAMY, V.B. HOSAGOUDAR*, T.K. ABRAHAM, (Indian Phytopathology, 2003)
During a survey of the foliicolous biotrophs in Thiruvananthapuram district of Kerala State, authors collected a black mildew fungus. Microscopic examination of the fungus revealed that it is hitherto undescribed species of the genus Meliola and hence the report.